Selective Hydrogen Production from Methanol with a Defined Iron Pincer Catalyst under Mild Conditions. Issue 52 (11th December 2013) - Alberico, Elisabetta; Sponholz, Peter; Cordes, Christoph; Nielsen, Martin; Drexler, Hans‐Joachim; Baumann, Wolfgang; Junge, Henrik; Beller, Matthias
Abstract Molecularly well‐defined iron pincer complexes promote the aqueous‐phase reforming of methanol to carbon dioxide and hydrogen, which is of interest in the context of a methanol and hydrogen economy. For the first time, the use of earth‐abundant iron complexes under mild conditions for efficient hydrogen generation from alcohols is demonstrated.